Test-retest reliability of single leg jump performance using the drift protocol in division I baseball pitchers - Bergquist, A. M.; Lebron, M. A.; Mangum, L. C.; Stout, J. R.; Fukuda, D. H. (Journal of Science in Sport and Exercise, 2025)
This study aimed to determine the test-retest reliability and efficacy of the Drift protocol. Thirteen male Division I Baseball pitchers (18-35 years.) completed four testing visits where a single leg hopping protocol on the stride and trail legs was completed with and without an arm swing. Jump contact time and flight time demonstrated "moderate to good" relative reliability (ICC = 0.633-0.847) and acceptable absolute reliability (CV = 3.6%-14.1%). The stride leg, compared to the trail leg, displayed greater relative and absolute reliability for contact time, flight time as well as jump power (ICC = 0.692-0.847; CV = 3.6%-14.1%). Arm swing trials demonstrated more acceptable relative and absolute reliability than trials without an arm swing for contact and flight time, jump height and jump power (ICC = 0.574-0.837; CV = 3.6%-9.3%). Significant main effects for arm swing were found for jump height, power, contact and flight time, and the average area covered (P < 0.001). Significant main effects were also found in asymmetry variables regarding arm swing for the variables jump height, power and flight time (P < 0.05). The current data suggest that, when assessing single leg vertical jumps in baseball pitchers with the Drift protocol, jump height, power, contact and flight time may be more reliable than average drift and total area covered.